Evaluation of Plasma Calcitonin Gene-Related Peptide as a Biomarker for Painful Temporomandibular Disorder and Migraine - Tchivileva IE; Johnson KW; Chai X; VanDam LR; Lim PF; Slade GD (Journal of Pain Research, 2023)
Inna E Tchivileva,1,2 Kirk W Johnson,3 Xiyun Chai,4 Lyndsey R VanDam,3 Pei Feng Lim,1,5 Gary D Slade1,6 1Center for Pain Research and Innovation, Adams School of Dentistry, University of North Carolina at Chapel Hill, Chapel Hill, NC, USA; 2Division of Oral and Craniofacial Health Sciences, Adams School of Dentistry, University of North Carolina at Chapel Hill, Chapel Hill, NC, USA; 3Pain Research, Eli Lilly and Company, Indianapolis, IN, USA; 4Precision Medicine Neuroscience, AbbVie, Chicago, IL, USA; 5Division of Diagnostic Sciences, Adams School of Dentistry, University of North Carolina at Chapel Hill, Chapel Hill, NC, USA; 6Division of Pediatric and Public Health, Adams School of Dentistry, University of North Carolina at Chapel Hill, Chapel Hill, NC, USACorrespondence: Inna E Tchivileva, Center for Pain Research and Innovation, Adams School of Dentistry, University of North Carolina at Chapel Hill, CB# 7455, Chapel Hill, NC, 275199-7455, USA, Tel +1 919 537 3291, Fax +1 919 966 5339, Email inna@unc.eduObjective: To assess associations of plasma calcitonin gene-related peptide (CGRP) with chronic temporomandibular disorder (TMD) myalgia/arthralgia or frequent/chronic migraine, alone and in combination, and to evaluate relations between the CGRP concentration and clinical, psychological, and somatosensory characteristics of participants.Methods: The cross-sectional study selected four groups of adult volunteers: healthy controls (HCs), TMD without migraine, migraine without TMD, and TMD with migraine. Each group comprised 20 participants, providing 94% power to detect statistically significant associations with CGRP concentration for either TMD or migraine. TMD and headache were classified according to the Diagnostic Criteria for TMD and the International Classification for Headache Disorders, 3rd edition, respectively. Plasma CGRP was quantified with a validated high-sensitivity electrochemiluminescent Meso Scale Discovery assay. Questionnaires and clinical examinations were used to evaluate characteristics of TMD, headache, psychological distress, and pressure pain sensitivity. Univariate regression models quantified associations of the CGRP concentration with TMD, migraine, and their interaction. Univariate associations of the CGRP concentration with clinical, psychological, and pressure pain characteristics were also assessed.Results: Among 80 participants enrolled, neither TMD nor migraine was associated with plasma CGRP concentration (P = 0.761 and P = 0.972, respectively). The CGRP concentration (mean ± SD) was similar in all 4 groups: HCs 2.0 ± 0.7 pg/mL, TMD 2.1 ± 0.8 pg/mL, migraine 2.1 ± 0.9 pg/mL, and TMD with migraine 2.2 ± 0.7 pg/mL. CGRP concentration was positively associated with age (P = 0.034) and marginally with body mass index (P = 0.080) but was unrelated to other participant characteristics.Conclusion: In this well-powered study, interictal plasma concentration of CGRP was a poor biomarker for TMD and migraine.Keywords: orofacial pain, musculoskeletal pain, neuropeptide, temporomandibular joint disorders, headache